ANALYSIS OF SCHEMES OF COMBINATION OF COORDINATE INFORMATION DECISION-MAKING IN THE INTEGRATED COLLISION PREVENTION SYSTEM - Нестерова, Л. М. (Proceedings of National Aviation University (archive), 2021)
The main tendencies of integration of flight support means are determined. The results of modeling the probabilistic characteristics of integrated systems are presented and the efficiency of different schemes of information combination is analyzed.